The effects of temperature on surfactant solution: A molecules dynamics simulation. Issue 1 (1st February 2022) - Feng, Pang; Wang, Linlin
Abstract: We use molecules dynamics simulation to investigate the effects of temperature on surfactant solution, both the microcosmic and macroscopic performance of the surfactant solution. Results show that the increase of temperature has bidirectional influence on the capability of the surfactant solution. From the microscopic point of view, the thermophoresis of the free water molecules has arisen in the forward of the temperature, which causes the hydrogen bonding between molecules fracture and reconnection. And the micelles keep close to and detached from each other for these. From a macro perspective, viscosity will decrease with temperature. But when the temperature is about 392.15K, the viscosity-temperature curve will have a peak value. Combining the micro results and macro results of the molecules dynamics simulation, we can clearly draw a conclusion that the effects of temperature on the surfactant solution never are monotonic.